The dynamics of the transpolar drift current - A. Constantin (Faculty of Mathematics, University of Vienna); R. S. Johnson (School of Mathematics, Statistics & Physics, Newcastle University) (Geophysical & Astrophysical Fluid Dynamics, 2024)
The abstract is available here: https://uscholar.univie.ac.at/o:2072341 The abstract is available here: https://uscholar.univie.ac.at/o:2072341